Prevalence of bacterial febrile illnesses in children in Kilosa district, Tanzania. - Beatrice Chipwaza; Ginethon G Mhamphi; Steve D Ngatunga; Majige Selemani; Mbaraka Amuri; Joseph P Mugasa; Paul S Gwakisa (Public Library of Science (PLoS), 2015)
INTRODUCTION:Bacterial etiologies of non-malaria febrile illnesses have significantly become important due to high mortality and morbidity, particularly in children. Despite their importance, there are few reports on the epidemiology of these diseases in Tanzania, and the true burden of such illnesses remains unknown. This study aimed to identify the prevalence of leptospirosis, brucellosis, typhoid fever and urinary tract infections and their rate of co-infections with malaria. METHODS:A cross-sectional study was conducted at Kilosa district hospital in Tanzania for 6 months. Febrile children aged from 2-13 years were recruited from the outpatient department. Patients were screened by serological tests such as IgM and IgG ELISA, and microscopic agglutination test. RESULTS:A total of 370 patients were enrolled; of these 85 (23.0%) had malaria parasites, 43 (11.6%) had presumptive acute leptospirosis and 26/200 (13%) had confirmed leptospirosis. Presumptive acute brucellosis due to B. abortus was identified among 26 (7.0%) of patients while B. melitensis was detected in 57 (15.4%) of the enrolled patients. Presumptive typhoid fever due to S. Typhi was identified in thirty eight (10.3%) of the participants and 69 (18.6%) had urinary tract infections. Patients presented with similar symptoms; therefore, the identification of these diseases could not be done based on clinical ground alone. Co-infections between malaria and bacterial febrile illnesses were observed in 146 patients (39.5%). Although antibacterials and/or anti-malarials were prescribed in most patients, some patients did not receive the appropriate treatment. CONCLUSION:The study has underscored the importance of febrile bacterial diseases including zoonoses such as leptospirosis and brucellosis in febrile children, and thus such illnesses should be considered by clinicians in the differential diagnoses of febrile diseases. However, access to diagnostic tests for discrimination of febrile illnesses is needed. This would allow febrile patients to receive the correct diagnoses and facilitation of accurate and prompt treatment.